Analysis of Social Return on Investment (SROI) at the Pijar Gemilang Community Development Program of PT PLN Nusantara Power Unit Pembangkitan Remban - Jayadi Jayadi; Bambang Apriyanto; Edi Saputra; Vernando Pratama Putra; Dimas Aji Prastyo (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
Objective of this study is to analyze the social investment impact of the PIJAR GEMILANG Community Development Program implemented by PT PLN Nusantara Power UP Rembang using the Social Return on Investment (SROI) approach. This program represents a waste-based social innovation initiative utilizing dragon fruit waste and FABA waste as raw materials for organic fertilizer and a farmer savings system, located in Trenggulunan Village, Pancur District, Rembang Regency. Methods employed a quantitative approach within the Social Innovation Impact Measurement (SIIM) framework using the SROI method. Data were collected through in-depth interviews with 15 involved stakeholders, field observations, and secondary document studies including strategic planning documents, monitoring and evaluation reports, and community satisfaction indexes. Data analysis proceeded through seven stages: stakeholder identification, program input mapping, outcome determination, impact monetization, present value calculation with discount rates of 6% (2023), 6% (2024), and 4.75% (2025), and SROI ratio calculation. Results indicate that the PIJAR GEMILANG Program involves 15 stakeholders with four primary community groups (KWT Lestari, KTH Parikesit, Pokdarwis PARTA, and BUMDes Unggul Sejahtera). Total investment value during the 2023–2025 period reached IDR 150,912,200, while total benefits generated reached IDR 432,341,526. The SROI ratio obtained was 2.86, meaning that every IDR 1 invested generates IDR 2.86 in social benefits. Tangible program impacts include 16.3 tons of waste managed (81.09%), increased income for KWT Lestari members of IDR 25,650,000 per year, the SERUNI farmer savings system valued at IDR 104,775,000, dragon fruit picking tourism income of IDR 72,000,000 per year for 15 farmers, and bokashi fertilizer savings of IDR 4,788,000.